Investigating Key Institutional Factors Affecting the Linkage of Knowledge Institutes with Farmers in Agricultural Research in Ethiopia - Bayissa, Debella Deressa (American Journal of Human Ecology, 2015)
Agriculture is the main sector that dominates Ethiopian economy. Agricultural research is the focus for poverty reduction and development. Agricultural research in Ethiopia has established itself on the ‘Green Revolution Model of Technology Development and Transfer’ undermining the institutional contexts. Lack of conducive institutional conditions is one of the factors impeding the linkage of researchers with farmers. Therefore, the objective of this study was to investigate critical factors hindering the linkage of knowledge institutes with farmers in agricultural research in Ethiopia. The research was conducted in Western Oromia using qualitative research approach. The data was primarily collected using in-depth interview. Respondents were identified through snowball sampling technique. The research revealed that institutional factors hindering the linkage of researchers with farmers include researchers’ limitation both in quality and quantity; financial problems; monopolization of the scarce resources; pipeline extension model; poor coordination; lack of culture to use local research results and weak rewarding system. The research concluded that resource shortage critically affected the linkage of researchers with farmers. Moreover, the linear extension system fundamentally hindered innovation. Furthermore, coordination among the different actors engaged in agricultural development was weak. Motivation system for outstanding researchers was not encouraging.